Norway spruce postglacial recolonization of Fennoscandia - Nota, Kevin; Klaminder, Jonatan; Milesi, Pascal; Bindler, Richard; Nobile, Alessandro; van Steijn, Tamara; Bertilsson, Stefan; Svensson, Brita; Hirota, Shun K.; Matsuo, Ayumi; Gunnarsson, Urban; Seppä, Heikki; et al. (Nature Communications, 2022)
Contrasting theories exist regarding how Norway spruce (Picea abies) recolonized Fennoscandia after the last glaciation and both early Holocene establishments from western microrefugia and late Holocene colonization from the east have been postulated. Here, we show that Norway spruce was present in southern Fennoscandia as early as 14.7 ± 0.1 cal. kyr BP and that the millennia-old clonal spruce trees present today in central Sweden likely arrived with an early Holocene migration from the east. Our findings are based on ancient sedimentary DNA from multiple European sites (N = 15) combined with nuclear and mitochondrial DNA analysis of ancient clonal (N = 135) and contemporary spruce forest trees (N = 129) from central Sweden. Our other findings imply that Norway spruce was present shortly after deglaciation at the margins of the Scandinavian Ice Sheet, and support previously disputed finds of pollen in southern Sweden claiming spruce establishment during the Lateglacial.